AN INNOVATIVE FINANCING INSTRUMENT TO PROMOTE THE DEVELOPMENT OF ISLAMIC MICROFINANCE THROUGH SOCIALLY RESPONSIBLE INVESTMENT SUKUK - Khouildi, Mohamed Yassine; Hj. Kassim, Salina (Journal of Islamic Monetary Economics and Finance, 2018)
Socially responsible investment (SRI) sukuk has a high potential to be an innovative financing mechanism for Islamic microfinance. This paper explores the possibility of implementing SRI sukuk for raising funds to support the microfinance industry and to promote financial inclusion. It also aims to identify the associated issues and challenges in implementing the SRI sukuk for microfinance purpose. The paper uses qualitative research method through a thorough review of existing literature, archives, and library research related to the area of social, sustainable and responsible investment sukuk, Islamic microfinance and their related issues. The SRI sukuk has a high potential to be developed as innovative shariah-compliant mechanism as shown by Malaysian experience in issuing the SRI sukuk to develop socially-related projects including the educational and green energy sectors. The paper also highlights and learn from the successful experience of the European Bank for Reconstruction and Development in issuing the first microfinance bonds. The findings from this study provide inputs to the relevant stakeholders in implementing new financial tools to develop the social sector, especially Islamic microfinance in helping the poor and assist them to become economically independent. New innovative tools for raising funds in microfinance is highly needed to achieve sustainability of the microfinance industry. Type of paper: Research paper